Information Visualization Human-Centered Issues and Perspectives - Kerren, Andreas; Stasko, John T.; Fekete, Jean-Daniel.; North, Chris; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book is the outcome of the Dagstuhl Seminar on "Information Visualization -- Human-Centered Issues in Visual Representation, Interaction, and Evaluation" held at Dagstuhl Castle, Germany, from May 28 to June 1, 2007. Information Visualization (InfoVis) is a relatively new research area, which focuses on the use of visualization techniques to help people understand and analyze data. This book documents and extends the findings and discussions of the various sessions in detail. The seven contributions cover the most important topics: There are general reflections on the value of information visualization; evaluating information visualizations; theoretical foundations of information visualization; teaching information visualization. And specific aspects on creation and collaboration: engaging new audiences for information visualization; process and pitfalls in writing information visualization research papers; and visual analytics: definition, process, and challenges.
General Reflections -- The Value of Information Visualization -- Evaluating Information Visualizations -- Theoretical Foundations of Information Visualization -- Teaching Information Visualization -- Specific Aspects -- Creation and Collaboration: Engaging New Audiences for Information Visualization -- Process and Pitfalls in Writing Information Visualization Research Papers -- Visual Analytics: Definition, Process, and Challenges.
Keywords: Computer science; Data mining; User interfaces (Computer systems).; Computer graphics; Computer Science; User Interfaces and Human Computer Interaction; Computer Graphics; Data Mining and Knowledge Discovery; Electronic books